AMPK: a therapeutic target of heart failure—not only metabolism regulation. Issue 1 (3rd January 2019) - Li, Xuan; Liu, Jia; Lu, Qingguo; Ren, Di; Sun, Xiaodong; Rousselle, Thomas; Tan, Yi; Li, Ji
Abstract : Heart failure (HF) is a serious disease with high mortality. The incidence of this disease has continued to increase over the past decade. All cardiovascular diseases causing dysfunction of various physiological processes can result in HF. AMP-activated protein kinase (AMPK), an energy sensor, has pleiotropic cardioprotective effects and plays a critical role in the progression of HF. In this review, we highlight that AMPK can not only improve the energy supply in the failing heart by promoting ATP production, but can also regulate several important physiological processes to restore heart function. In addition, we discuss some aspects of some potential clinical drugs which have effects on AMPK activation and may have value in treating HF. More studies, especially clinical trials, should be done to evaluate manipulation of AMPK activation as a potential means of treating HF.